New humidity control material prepared from the sintering of diatomite, waste glass and cockle shells to balance indoor relative humidity - Huong, Pei Zam (2022)
Introduction: High relative humidity (RH) in buildings leading to mould growth and exposure is a health risk. Conventionally, the buildings in Malaysia used airconditioning and mechanical ventilation (ACMV) system to control indoor RH. However, it does not help in balancing the high RH buildup in an air-conditioned office when the efficiency of dehumidifying of ACMV system is decreased due to excessive cooling to lower the indoor temperature. This study aimed to determine the RH in 32 selected air-conditioned offices and the associated health effects among 294 office respondents located in the public university buildings. This study also aims to develop a humidity control material (HCM) and characterize the properties of the material. Methodology: RH of each office room was recorded using TSI Velocicalc for 30 minutes at four time slots and calculated the average. Health symptoms were accessed via modified, selfadministered questionnaire from Indoor Air Quality and Work Environment Symptoms Survey, NIOSH Indoor Air Quality Survey (1991). For the material, a mixture of diatomite, waste glass and cockle shell powder with specific ratio was sintered at 1100°C for 20 minutes in the Muffle furnace. The chemical compositions of diatomite, cockle shell powder and waste glass were determined using Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). Moisture adsorption-desorption performances was tested referring to JIS A 1475-2004 procedure. Porous properties were determined through surface area analyser. Scanning Electron Microscope (SEM) Images and Energy Dispersive X-Ray (EDX) Analysis was used to assessed the surface morphology of the samples. Flexural strength of samples was tested using Universal Testing Machine. Antibacterial capability of samples was tested using disc diffusion test against Staphylococcus aureus and Pseudomonas aeruginosa. Results: The average relative humidity of 32 offices were 68.4% with maximum 72% and minimum 64.9%. There were five rooms with RH more than 70% does not comply with the permissible range stated in Industry Code of Practice for Indoor Air Quality. A total of 27.4, 28.0, 28.5, 34.2, 31.4 and 29.1% building occupants had headache, runny nose, sore throat, unusual fatigue, sleepiness, and fever respectively. The prevalence of SBS calculated was 35.6%. The results from multiple logistic regressions shows that an increase in average RH was associated with a twofold increase in the reporting of Sick Building Syndrome (SBS) (OR 2.38; 95% CI 1.21-4.69). Respondents who perceived the room temperature was too hot were 0.47 times less likely to complain about having SBS (OR 0.47: 95% CI 0.29-0.77). Likewise, respondents who were satisfied with the overall thermal comfort was 0.54 times less probably to report health symptoms (OR 0.54; 95% CI 0.34-0.85). Diatomite is mainly made up of SiO2 (89.78%) and waste glass also have high content of SiO2 at 68.46%. Main chemical component of cockle shell is calcium carbonate (CaCO3) with 98.67%. The sintered materials have specific surface area from 5.744 m2/g to 14.765 m2/g, total pore volume recorded from 0.028-0.08 cm3/g and pore size range from 39.5-67.7 nm. The moisture adsorption-desorption results indicated that the best material, manufactured by mixing 60% diatomite, 30% waste glass and 10% cockle shell powder. The 48h moisture adsorbed amount of compacted sample reached 7.95 % at 75% RH. The flexural strength of 8.23 ± 1.8 MPa satisfy the standard of those commercial porous ceramics. Moisture adsorption-desorption ability of the humidity control materials increases as diatomite content increases. The substitution of waste glass up to 30% showed a significant enhancement of strength in compacted samples till 80%. Qualitatively, all the sintered samples had inhibition on gram-positive Staphylococcus aureus and gram-negative Pseudomonas aeruginosa. Conclusion: The average RH of offices was within the recommended range according to Malaysian Code of Practice. The prevalence of SBS was 35.6% with unusual fatigue as the highest reported symptom. The increase in average RH over 68.4% was a significant contributor towards the occurrence of health symptoms among respondents. The compacted samples showed excellent properties and highly promising for various construction applications. There is a need to ensure regular maintenance of ventilation system coupling with innovative indoor humidity control measures to provide a safe and healthy work environment.